5,13-Bis(4-methoxyphenyl)dinaphtho[2,3-b:2′,3′-d]thiophene S,S-dioxide dichloromethane hemisolvate - R. Manickam; G. Jagadeesan; S. Muhamad Rafiq; A. K. Mohanakrishnan; G. Srinivasan (IUCrData, 2019)
The title compound, C34H24O4S·0.5CH2Cl2, crystallizes with two independent molecules and one dichloromethane solvent molecule in the asymmetric unit. The crystal packing is consolidated by C—H...O hydrogen bonds.